Sport Motivation of Paralympic Athletes after Injury - D Deasyanti; J Juriana; Sambadha Adhi Prasetyo (Universitas Pendidikan Indonesia, 2021)
Motivation for performing sport is complex because most athletes have multiple motivations, including extrinsic and intrinsic motivation. Understanding the motivation dynamics of athletes, especially after a sports injury, is crucial because the injury may have a detrimental effect on the athlete's psychosocial conditions. This study figured out the motivation level of Paralympic athletics athletes after injury. A total of 44 Paralympic athletes were involved in the survey. The Sports Motivation Scale (SMS) was used to identify the level of athlete motivation. The SMS was developed within the Self Determination Theory (SDT) framework to assess various forms of motivation, namely amotivation, external regulation, introjected regulation, identified regulation, integrated regulation, and intrinsic motivation. This study found that out of 44 Paralympic athletics athletes after an injury, 5 (4.55%) of the athletes reported high levels of amotivation, and 15 (34.09%) of the athletes were identified in the moderate level of amotivation. This finding indicates that injury does not impact amotivation, as the athletes exhibit a high level of extrinsic motivation (external regulation, introjected regulation, identified regulation, integrated regulation) and intrinsic motivation. Based on these motivation profiles, the Paralympic coaches should adjust their approach in motivating the Paralympic athletes to return to their training and competitions after injury.